Chronic Postoperative Endophthalmitis: A Review of Clinical Characteristics, Microbiology, Treatment Strategies, and Outcomes - Fadi Maalouf; Marwan Abdulaal; Rola N. Hamam (Hindawi Limited, 2012)
Chronic postoperative endophthalmitis (CPE) is a delayed infectious intraocular inflammation process that occurs more than six weeks after ocular surgery and frequently masquerades as autoimmune uveitis. These cases are at risk of delayed diagnosis and erroneous long-term treatment with corticosteroids. This paper aims to review the epidemiology, microbiology, clinical characteristics, diagnosis, management strategies, and outcome of chronic postoperative endophthalmitis. The incidence of CPE is still uncommon, and multiple pathogens have been reported with varying frequencies. Review of the literature reveals that CPE cases have a high incidence of visual impairment and recurrence rate might be decreased with aggressive surgical approach.